Developing Social Media-Based Textbook for Speaking Class in English Study Program: Pengembangan Buku Ajar Berbasis Media Sosial untuk Kelas Berbicara di Program Studi Bahasa Inggris - Marleni, Lusi; Asilestari, Putri (Universitas Muhammadiyah Sidoarjo, 2019)
Lack of reference, guidelines, facilities, time and place of practice English become the problems of this research. This study aims to develop textbook based on social media which is used in Speaking Class at English Study Program. The research adapted some steps of the development by Ploomp which included Need Analysis, Self-Evaluation, Expert Review, Small Group Evaluation, Field Test, and assessment phase. The product of this research is a textbook which consisted of fourteen chapters. Each chapter applied speaking activities through social media. The materials written based on social media and taught by using social media included; Facebook, Whatsapp, Instagram, and Youtube. The textbook is developed and implemented based on social media in accordance with the competency standards set in the curriculum of department. The training materials and activities by using social media strongly guide students to practice English and provide a different atmosphere in the learning process.